The Territorial Frames of a Small Town in the Landuse System Ensuring its Sustainable Development - ROGATNEV, Yury Mikhailovich; VESELOVA, Marina Nikolaevna; KHORECHKO, Irina Vladimirovna; FILIPPOVA, Tatyana Anatolievna; SHCHERBA, Valentina Nikolaevna (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).15, 2017)
The aim of this research is the development of scientific and methodological provisions on the nature and structure of territorial frames, as a reflection of the land use system. The objectives are the analysis and assessment of urban land and property complex to develop solutions to improve the use of land and to ensure the sustainable development of small towns based on an assessment of identified features of the state of its territorial frames. The subject of the study is the set of land and property relations arising in the process of sustainable development of small towns, the processes that change the state of the land and determine the system of land use. The study used the methods of analysis and synthesis, statistical and monographic methods. The scientific significance of the work lies in the proposal to consider the arrangement of land use of a small town in view of its basic territorial frames, which allow a more accurate assessment of the current structure of urban land, and socio-economic conditions of urban areas, enabling to develop on this basis some proposals to ensure their sustainable development. The content of environmental, economic, social, land and property frames has been formulated. Their peculiarities in the conditions of a small town have been identified. The paper describes a method of analyzing the conditions of land use and urban land use system through the parameters of territorial frames. The prospects of urban land use development were identified based on improving environmental, economic and social frames. It has been shown that the results of these activities are fixed through formation of a new state of the land and property complex (frame) of the town.